Effect of cinnamon extraction oil (CEO) for algae biofilm shelf-life prolongation - Othman, Maizatulnisa; Rashid, Haziq; Jamal, Nur Ayuni; Shaharuddin, Sharifah Imihezri; Sulaiman, Sarina; Hairil, H. Saffiyah; Khalid, Khalisanni; Zakaria, Nazarudin (MDPI, 2019)
This study was conducted to improve the life-span of the biofilm produced from algae by evaluating the decomposition rate with the effect of the cinnamon extraction oil (CEO). The biofilm was fabricated using the solution casting technique. The soil burying analysis, demonstrated low moisture absorption of the biofilm thus decelerating the degradation due to low swelling rate and microorganism activity hence, prolong the shelf-life of the biofilm. Hence, the addition of CEO also affects the strength property of the biofilm. The maximum tensile strength was achieved with the addition of 5% CEO which indicated a good intermolecular interaction between the biopolymer (algae) and cinnamon molecules. The tensile strength which was measured at 4.80 MPa correlated with the morphological structure. The latter was performed using SEM, where, the surface showed the absence of a separating phase between the biofilm and cinnamon blend. This was evidenced by FTIR analysis which confirmed the occurrence of no chemical reaction between the biofilm and CEO during processing. The prolongation shelf-life rate of biofilm with good tensile properties are achievable with the addition of 5% of CEO.